On the composition of Brazilian tobacco seed oils - Lago, Regina C.A.; Kazan, E.; Nogueira, Francisco D.; Cosenza, M. L. (Pesquisa Agropecuaria Brasileira, 2014)
Tobacco seeds of Nicotiana tabacum L. and Nicotiana rustica L. Species were studied regarding protein and oil contents. Fatty acid composition of tobacco seed oils was determined, through as chromatography. The percentage of linoleic acid, the main fatty component, was found to lie between 65.0 and 74.3. It is reported, for the first time, the occurrence of erucic acid, in a percentage higher than trace, but only for two samples. Only with respect to the colour it was observed a difference between oils from the two species.